2019
DOI: 10.1111/jocd.13173
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of lead and selenium in patients with premature graying of the hair

Abstract: Hair graying is a natural occurring process of aging. However, when it happens prematurely it can be an esthetic problem causing low self-esteem and social acceptability leading to psychological issues. Moreover, several studies have found associations between premature hair graying (PHG) and several more serious conditions such as osteopenia, coronary artery disease, and autoimmune disorders. 1-3 As a rule of thumb, 50% of hairs of 50% of people older than 50 years are gray 4 ; however, recent studies showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Among mineral deficiencies, significant association was seen between PGH and low serum calcium and ferritin levels (Figure 3). There was exception for the levels of lead and selenium where Kiafar et al 49 showed no significant difference in patients with and without PHG.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Among mineral deficiencies, significant association was seen between PGH and low serum calcium and ferritin levels (Figure 3). There was exception for the levels of lead and selenium where Kiafar et al 49 showed no significant difference in patients with and without PHG.…”
Section: Resultsmentioning
confidence: 92%
“…Positive family history (of at least one family member) was present in 25.3‐90% 1,25,29,37,47‐49,56,58,59 . Family history of PGH was found in 55.8% (1st degree), 25% (2nd degree) and 38.4% (3rd degree) relatives among Indian PGH patients 1 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation